The Copepoda mitogenome as a dynamic evolutionary landscape - Javier Urban-Olivares; Elizabeth Ortega-Mayagoitia; José Arturo Alcántara-Rodríguez; Nohemi Dimas-Flores; Alejandra Rougon-Cardoso; Jorge Ciros-Pérez (PLoS ONE, 2026)
Copepods are an extraordinarily diverse group that exhibit a broad spectrum of morphological, physiological, life-history traits, and habitat specializations. Despite their ecological, evolutionary, and economic importance, molecular resources are scarce, limiting our understanding of their diversification and adaptation. We analysed the evolution of copepod mitogenomes at different phylogenetic scales using 19 complete mitogenomes deposited in GenBank along with five de novo assemblies from species of the genus Leptodiaptomus from Central Mexico. All five new mitogenomes are circularized and include all canonical metazoan coding regions but differ in the composition and size of non-coding regions (NCRs). The mitochondrial genomes of the four populations of the L. sicilis -group are the largest reported to date in Copepoda (>36,000 bp). The NCRs of Leptodiaptomus spp. contain repeated regions, pseudogenes, long palindromes with secondary structures, and open reading frames, although much of their content is still unexplained. Gene ordering in Copepoda is highly dynamic, and even gene blocks highly conserved across metazoans are either absent or occur at a low frequency. In Calanoida, the NCRs have expanded considerably, whereas in podoplean clades (Cyclopoida, Harpacticoida, and Siphonostomatoida), they remain similar to the hypothetical ancestral state. While some genes display evident signatures of purifying selection, most exhibit evidence of positive selection across all branches of the phylogeny. These findings offer a basis for further research on the molecular mechanisms driving copepod adaptation and diversification, as well as for refining predictions of their responses to environmental change.